SIKAP KONSUMEN TERHADAP PRODUK BUNDLING AGRIBISNIS - Junaedi, Didi; Setyawan, Anton Agus; Soepatini, Soepatini (Jurnal Manajemen Dayasaing, 2016)
The objectives of the study are how to determine product bundling strategy andimplementation to Dekalb brand hybrid corn and Round-up brand herbicide. By analyzes how consumer attitudes toward buying intention in this regard farmers as buyer and retailers as products services. The data used is primary data. Primary data is obtained using 2 kind of respondents are retailers and farmers. The data obtained by distributed 30 questionnaires for retailers and 110 farmers in Grobogan. The descriptive statistic employed to analyzed data by using multiple linear regressions with t test, F test and coefficient of determination. The result showed that on retailers respondents attribute the product bundling has no significant influence to consumer buying intention but consumer attitudes significantly influence the buying intention. On the farmers respondents showed that attributes of the product bundling and consumer attitudes positive and significant influence to buying intention.